Analysis of dentin/enamel remineralization by a CPP‐ACP paste: AFM and SEM study. Issue 6 (20th February 2013) - Poggio, Claudio; Lombardini, Marco; Vigorelli, Paolo; Ceci, Matteo
Summary The aim of the present in vitro study was the evaluation of a CPP‐ACP paste on preventing dentin/enamel erosion produced by a soft drink; Atomic Force Microscopy and Scanning Electron Microscopy were used. Eighty extracted human incisors free of caries were selected and divided into four groups (each divided in two subgroups); group 1a: intact dentin; group 1b: dentin + soft drink; group 2a: intact dentin + CCP‐ACP paste; group 2b: dentin + soft drink + CCP‐ACP paste; group 3a: intact enamel; group 3b: enamel + soft drink; group 4a: intact enamel + CCP‐ACP paste; group 4b: enamel + soft drink + CCP‐ACP paste. The CPP‐ACP paste was applied for 3 min at 0, 8, 24, and 36 h. The surface of each dentin/enamel specimen was imaged by AFM (Rrms values were registered) and SEM. A statistical significant difference was recorded between groups 1b (dentin + soft drink) and 2b (dentin + soft drink + CCP‐ACP paste) and between groups 3b (enamel + soft drink) and 4b (enamel + soft drink + CCP‐ACP paste), suggesting that treatment of the specimens with the CPP‐ACP paste had a protective effect on enamel demineralization, which was more evident for enamel specimens. Under the limitations of the present in vitro study, it can be concluded that the application of a CPP‐ACP paste is effective on preventing dentin/enamel erosion produced by a soft drink. SCANNING 35:366–374, 2013. © 2013 Wiley Periodicals, Inc. SCANNING 35:???–???, 2013. © 2013 Wiley Periodicals, Inc.